Trends in incidence and mortality of colorectal cancer and related life loss in Haishu District， Ningbo of Zhejiang Province， 2017‒2022 - SHEN Yingzhuo; CHEN Jie; ZHANG Peiling (Shanghai yufang yixue)
ObjectiveTo analyze the trend of incidence, mortality rate and related life loss of colorectal cancer in Haishu District, Ningbo from 2017 to 2022, so as to provide a scientific basis for the prevention and treatment of colorectal cancer.MethodsThe incidence and death data of colorectal cancer among residents in Haishu District during 2017‒2022 were collected from the Ningbo Municipal Digital Disease Prevention and Control Platform. The incidence and mortality rate, the age-specific incidence and mortality rate, potential years of life lost (PYLL), potential years of life lost rate (PYLLR), and average years of life lost (AYLL) were calculated. The standardized rate was calculated based on the standardized population from the Sixth National Census in 2010, and the annual percentage change (APC) was calculated by Joinpoint Regression Program.ResultsA total of 2 595 cases of colorectal cancer were reported in Haishu District from 2017 to 2022, with a crude incidence rate of 68.23/100 000 and a standardized incidence rate of 39.72/100 000. There were no statistical differences in crude and standardized incidence rates(APC=2.288%, -0.160%,both P>0.05). In addition, a total of 898 colorectal cancer deaths were reported, with a crude mortality rate of 23.61/100 000 and a standardized mortality rate of 12.18/100 000, of which the crude mortality rate and standardized mortality rate of males showed an upward trend (APC=10.855%, 7.895%, both P<0.05). Furthermore, the crude incidence and mortality rate of colorectal cancer in males were higher than those in females (both P<0.05). The crude incidence and mortality rate of colorectal cancer in Haishu District showed an increasing trend by age (both P<0.05). PYLL caused by colorectal cancer was 7 818.52 person-years, and AYLL was 8.71 years, with a PYLLR of 2.06‰.ConclusionThe incidence and mortality rate of colorectal cancer in Haishu District are still at a high level. Colorectal cancer screening should be continued, relevant health knowledge should be facilitated and disseminated, awareness of early screening and diagnosis of colorectal cancer should be promoted, and ultimately improving the survival rate of the patients.